Do patients with femoroacetabular impingement syndrome who undergo hip arthroscopy display improved alpha angle (magnetic resonance imaging) and radiographic hip morphology?. (11th December 2022) - Thirumaran, Aricia Jieqi; Murphy, Nicholas J; Eyles, Jillian Peta; Linklater, James M.; Reichenbach, Stephan; Schmaranzer, Florian; Lerch, Till D.; Venkatesha, Venkatesha; Heller, Gillian; O'Donnell, John; Hunter, David J.
Abstract: Aims: To compare (a) the change in radiological bony morphology between participants with femoroacetabular impingement (FAI) syndrome who underwent arthroscopic hip surgery compared to physiotherapist‐led non‐surgical care and (b) the change in radiological bony morphology between participants with FAI syndrome who underwent arthroscopic hip surgery involving cam resection or acetabular rim trimming or combined cam resection and acetabular rim trimming. Methods: Maximum alpha angle measurements on magnetic resonance imaging and Hip 2 Norm standardized hip measurements on radiographs were recorded at baseline and at 12 months postoperatively. One‐way analysis of covariance and independent T tests were conducted between participants who underwent arthroscopic hip surgery and physiotherapist‐led non‐surgical care. Independent T tests and analysis of variance were conducted between participants who underwent the 3 different arthroscopic hip procedures. Results: Arthroscopic hip surgery resulted in significant improvements to mean alpha angle measurements (decreased from 70.8° to 62.1°) ( P value < .001, 95% CI −11.776, −4.772), lateral center edge angle (LCEA) ( P value = .030, 95% CI −3.403, −0.180) and extrusion index ( P value = 0.002, 95% CI 0.882, 3.968) compared to physiotherapist‐led management. Mean maximum 1‐year postoperative alpha angle was 59.0° ( P value = .003, 95% CI 4.845, 18.768) for participants who underwent isolated cam resection. Measurements comparing the 3 different arthroscopic hip procedures only differed in total femoral head coverage (F[2, 37] = 3.470, P  = .042). Conclusion: Arthroscopic hip surgery resulted in statistically significant improvements to LCEA, extrusion index and alpha angle as compared to physiotherapist‐led management. Measured outcomes between participants who underwent cam resection and/or acetabular rim trimming only differed in total femoral head coverage.